Cohen's pathways of the pulp - Berman, L. H. Louis H.; Hargreaves, K. M. Kenneth M.; Rotstein, I. Ilan (Elsevier, 2021)
Stay up on the latest research and techniques in endodontics with Cohen's Pathways of the Pulp, 12th Edition. Written by a team of internationally renowned experts and trusted for more than 40 years, this definitive guide covers the science, theory, and practice of endodontics. Full color illustrations and detailed radiographs guide readers through each step of endodontic care - from diagnosis and treatment planning to proven techniques for managing pulpal and periapical diseases. This new twelfth edition also boasts the very latest evidence-based research and techniques, reorganized and condensed chapters, plus other features designed to help you locate important information quickly and easily. Complete with access to Expert Consult, it's everything you need to stay ahead in the field of endodontics. Extensive illustration collection includes over 2,000 full-color photos, line art, and radiographs to clearly demonstrate core concepts and reinforce the essential principles and techniques of endodontics. Video clips and case studies demonstrate key procedures such as palpation of the masseter muscle, introsseous anesthesia with the X-tip system, dentin hypersensitivity, and more. Diverse and respected contributor pool includes experts from many national- and international-based dental education programs. NEW! Updated content and new images incorporate the most recent developments in research and clinical endodontic techniques. NEW! Additional topics cover pulp biology, pathobiology, diagnosis, treatment planning, pain control, isolation, access, cleaning and shaping, obturation, restoration, assessment of outcomes, emergencies and surgery. Each online topic comes with assigned reading lists, a PowerPoint lecture, written lesson objectives, and example exam questions. NEW! Compliance with the Commission on Dental Accreditation Curriculum ensures that the needs of all dental programs are met. NEW! Reorganized sections now divide chapters by those covering clinical endodontics, those covering the biological basis of endodontics, and chapters which detail endodontics in private practice to make content easier for both clinicians and students to navigate. NEW! Condensed chapters remove unnecessary duplication of content across the text and make the physical text lighter and easier to use.